Analisa Pengaruh Penambahan Unsur Cu (Tembaga) Terhadap Sifat Mekanis Al – Si Melalui Proses Casting - Samhuddin; Al Ichlas Imran (Piston: Jurnal Teknologi, 2021)
The purpose of this study is to determine the effect of the elements copper (Cu) on the mechanical properties of aluminum silicon (Al-Si). The mechanical properties of aluminum are lightweight, low temperature, corrosion resistance, mechanical properties vary (strength, hardness and ductility), good formability, and capable of a good cast. While the mechanical properties of copper are formability, good electrical conductivity, good thermal conductivity, good corrosion resistance, has a density of 8.93 g / cm³, the modulus of elasticity of 115 GPa and liquid temperature 1083 ° C. Materials used were Al-Si and the element copper alloy. The addition of the element copper (Cu) amounting to, 2%, 4%, 6% and 8%. Manufacturing of specimens with sand casting process. Mechanical testing were hardness and impact. In this study get the biggest hardness value alloy Al - Si addressed by the addition of Cu 0% or without alloy of 96.53 Kg / mm2, while the lowest hardness value of alloy Al - Si indicated by the addition of 2% Cu at 63.74 Kg / mm² , The strength values impack alloy Al - Si addressed by the addition of 8% Cu 0.026 J / mm2, while the value of impact strength low alloy Al - Si Cu indicated by the addition of 6% of 0,018 J / mm².